Elucidation of the roles of ionic liquid in co2 electrochemical reduction to value-added chemicals and fuels - Mohammed, S.A.S. (MDPI, 2021)
The electrochemical reduction of carbon dioxide (CO2ER) is amongst one the most prom-ising technologies to reduce greenhouse gas emissions since carbon dioxide (CO2) can be converted to value-added products. Moreover, the possibility of using a renewable source of energy makes this process environmentally compelling. CO2ER in ionic liquids (ILs) has recently attracted atten-tion due to its unique properties in reducing overpotential and raising faradaic efficiency. The current literature on CO2ER mainly reports on the effect of structures, physical and chemical interac-tions, acidity, and the electrodeâelectrolyte interface region on the reaction mechanism. However, in this work, new insights are presented for the CO2ER reaction mechanism that are based on the molecular interactions of the ILs and their physicochemical properties. This new insight will open possibilities for the utilization of new types of ionic liquids. Additionally, the roles of anions, cati-ons, and the electrodes in the CO2ER reactions are also reviewed. Â© 2021 by the authors. Li-censee MDPI, Basel, Switzerland.